Synchronization of voltage frequency converters with the grid in the presence of notching. Issue 3 (5th May 2015) - Zieliński, Dariusz; Lipnicki, Piotr; Jarzyna, Wojciech
Abstract : Purpose: – In the dispersed generation system, power electronic converters allow for coupling between energy sources and the power grid. The requirements of Transmission System Operators are difficult to meet when the share of distributed energy sources of the total energy balance increases. These requirements allow to increase penetration of distributed generation sources without compromising power system stability and reliability. Therefore, in addition to control of active or reactive power, as well as voltage and frequency stabilization, the modern power electronic converters should support power grid in dynamic states or in the presence of nonlinear distortions. The paper aims to discuss these issues. Design/methodology/approach: – The research methodology used in this paper is based on three steps: Mathematical modelling and simulation studies, Experiments on laboratory test stand, Analyzing obtained results, evaluating them and formulating the conclusions. Findings: – The authors identified two algorithms, αβ-Filter and Voltage Controlled Oscillator, which are able to successfully cope with notch distortions. Other algorithms, used previously for voltage dips, operate improperly when the voltage grid has notching disturbances. This work evaluates six different synchronization algorithms with respect to the abilities to deal with notching. Research limitations/implications: – The paper presents results of the synchronization algorithms in the presence of nonlinear notching interference. These studies were performed using the original hardware-software power grid emulator, real-time d'Space platform and power electronic converter. This methodology allowed us to exactly and accurately evaluate synchronization performance methods in the presence of complex nonlinear phenomena in power grid and power electronic converter. The results demonstrated that the best algorithms were αβ – Filtering and Voltage Controlled Oscilator. Originality/value: – In this paper, different synchronization algorithms have been tested. These included the classical Phase Locked Loop with Synchronous Reference Frame as well as modified algorithms developed by the authors, which displayed high robustness with respect to the notching interference. During the tests, the previously developed original test rig was used, allowing software-hardware emulation of grid phenomena.